Nanotechnology in the improvement of local anesthetics - Bolzan, Alexandre Galina; Neto, Odone Gino Zago; de Oliveira, Jivago Schumacher; Rech, Virginia Cielo; Mortari, Sergio Roberto (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
Local anesthetics are widely used in regional blocks during surgical procedures, in postoperative pain relief, acute or chronic pain management, and even oncological therapies. However, these conventional local anesthetic agents present several disadvantages, such as neurotoxicity, short duration of action, and uncontrolled release, which restrict their application in clinical practice. This literature review explored recent advances in using nano-structured topical anesthetics, highlighting the benefits of nanotechnology-based formulations. The methodology involved the analysis of scientific publications from the last ten years. Nanotechnology management strategies have advanced considerably, mainly due to their low systemic toxicity and the enhanced efficacy of unconventional local anesthetics. Different nanometric-scale materials, including polymers, lipids (such as solid lipid nanoparticles, nanostructured lipid carriers, and nanoemulsions), metallic nanoparticles, non-metallic inorganic nanoparticles, and hybrid nanoparticles, can be used to treat and control pain in a safe, localized way.